Value of Indirect Benefits of Mangrove Forests as Coastal Abrasion Protectors - Ismail N Adam; Faizal Kasim; Citra Panigoro (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the value of indirect benefits of mangrove forests as a barrier to coastal abrasion and identify losses after abrasion in Limbatihu Village, Paguyaman Pantai District. The research was conducted in February to July 2016. The research method was observation and interviews with the community as respondents regarding the costs of damage and the construction of wave barriers. Observations were also made on the impact of losses due to loss of residence, land damage and damage to housing. The results showed that the indirect benefit value of wave and current barrier was IDR. 255,414,000 / year. The types of ownership losses due to abrasion are loss of residence (averagely IDR. 28,928,000,-) the loss on damage to land is averagely IDR 3,396,250,- and the loss on damage to dwelling place averagely IDR. 2,939,833,-. Keywords: mangrove forest; indirect benefits; abrasion.